Why is Absenteeism Low among Public Health Workers in Lao PDR? - Yamada, Hiroyuki; Sawada, Yasuyuki; Luo, Xubei (Taylor and Francis, 2013)
Absenteeism among public health workers is common in developing countries. Absence rates among public health workers are above 25 per cent in the five developing countries that Chaudhury et al. (N. Chaudhury, J. Hammer, M. Kremer, K. Muralidharan, and F.H. Rogers (2006) Missing in action: Teacher and health worker absence in developing countries. Journal of Economic Perspectives, 20, pp. 91–116) examined. However, the present study finds that the corresponding rate in Lao PDR is significantly lower (17%). Using a new dataset from the Lao PDR Public Expenditure Tracking Survey, we find that both extrinsic motivation and intrinsic motivation affect health centre worker behaviour: the timely payment of wages, a nonrural workplace and proximity of the workplace to hometown are factors that are negatively associated with absenteeism.